Življenje ob in po zdravljenju raka - pomen in možnosti psihosocialne rehabilitacije - Radonjič-Miholič, Vesna (Rehabilitacija (Ljubljana), 2008)
Cancer is a disease where physical and psychological aspects are significantly interconnected. The psychological aspects play their role in the onset and the course of the disease, and their role becomes even more important in the recovery and in the assurance of higher quality of life during and after the treatment. Patients with cancer must often face consequences of the disease, an uncertain prognosis, stressful treatment and prejudice against the disease (distrust, patronizing attitude). The quality of life can be importantly improved by recovered self-confidence, emotional stability, newly established values, social contacts and lifestyle. Therefore, the main goals of psychosocial rehabilitation include: psychological support, social skills training, vocational rehabilitation and help in ensuring effective support in the social environment. The programs of psychosocial rehabilitation are dynamic and require their continuation for a long period of time.
Keywords: bolniki; psihologija; psihosocialna rehabilitacija; rak (medicina); rehabilitacija; zdravljenje